Hubungan Antara Kualitas & Kuantitas Riwayat Kunjungan Antenatal Care (ANC) Dengan Stunting Pada Balita Usia 24-59 Bulan Di Kecamatan Pujon Kabupaten Malang - Camelia, Vita; Proborini, Astri; Jannah, Miftahul (Journal of Issues in Midwifery)
ABSTRACTStunting is a children growth problem that occurs a result of chronic malnutrition in the first 1000 days of life. The indicator of stunting is using the height measurement according to age HFA (Height for Age) under -2 SD based on the WHO growth standard curve according to sex. The impacts of stunting are the occurrence of growth disorders, barriers to development and the risk of metabolic disorders in adulthood. One of the risk factors for stunting is history of quality and quantity Antenatal Care (ANC). This study aimed to determine the relationship between quality and quantity history of ANC visits and stunting in toddlers aged 24-59 years in Pujon District Malang Regency. The method used in this research was observational analytic by using cross-sectional design. The population of this study was all mothers who have children aged 24-59 months that were conducted in January 2020. Ninety eight respondents taken by purposive sampling as the sample of the research. The data was obtained by filling out questionnaires and KIA books, then analyzed with chi-square test (Î± = 0.05). The results showed that there was a significant relationship in quality (p-value = 0.004) and quantity (p-value = 0.003) toward stunting.Keywords: Quality and Quantity of Antenatal Care (ANC), Stunting